(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Assessing the effectiveness of the deposit policy of Ukrainian banks in wartime is a strategically important task for ensuring the banking system’s stability, maintaining public confidence, and developing the economy as a whole. Purpose: substantiation of methodical approaches to assessing the deposit policy of commercial banks of Ukraine in martial law conditions. Methods. In the research process, the following general scientific methods of knowledge were used, such as: generalization and comparison (to compare the existing methods of assessing the effectiveness of the deposit policy of banks and to determine the most optimal one in modern conditions), analysis (to study changes in the structure of the deposit portfolio of Ukrainian banks and the directions of investing the funds involved in conditions of martial law) statistical method (when calculating indicators of the efficiency of the deposit policy of the Oschadbank). Results. The article summarizes methodical approaches to assessing the deposit policy of commercial banks of Ukraine in martial law conditions. The advantages and disadvantages of existing methods are analyzed. The expediency of using the evaluation methodology, which takes into account the structure of the involved resources and the directions of using deposit resources, is justified. The effectiveness of the deposit policy of the state bank Oschadbank in 2021-2023 is assessed. Conclusions. From the point of view of the profitability of using borrowed funds, Oschadbank’s deposit policy is effective, however, the need for its improvement is indicated by: a decrease in the proportion of term resources, the allocation of the majority of borrowed funds to the government bonds and deposit certificates, which negatively affect the activation of lending to the economy.